Current perceptions of strength and conditioning coaches use of sled tow training - Williams, J.; Baghurst, T.; Cahill, M. J. (International Journal of Sports Science & Coaching, 2021)
The purpose of this study was to assess current perceptions of strength and conditioning coaches` use of sled towing (ST) as part of their training programs. One-hundred and twenty-five coaches responded to a survey of their ST practices. Themes investigated included the primary purpose and usefulness of using ST, the loads used in short and long distances, rest times between sprints, total volume of ST sprints per session, frequency of ST activity each month, and whether coaches engaged in force-velocity profiling in ST sprints. Eighty percent of coaches either agreed or strongly agreed that ST is a useful intervention tool for improving athletic performance. Speed strength was the physiological adaptation most sought after to improve (n = 75) followed by power (n = 72). Bodyweight (BW) loads of 20% were the most common across all distances. The two most common rest times given between each ST repetition were one to two minutes (n = 37) and two to three minutes (n = 37). The most common volume responses for individual training sessions were five to eight sprints (n = 52) and three to five times per month, respectively. These data suggest strength and conditioning coaches view ST as an integral part of programming, primarily use loads of 20% BW for both short and long sprints and seek to optimize a number of different physiological adaptations. The majority of coaches have a favorable view of ST (88%); however, current training parameters used by strength and conditioning coaches may be inadequate to achieve their desired adaptations.